Effects of psoralen on hepatic bile acid transporters in rats. (June 2021) - Huang, Juyang; Wang, Qin; Chen, Mengying; Bi, Yanan; Shi, Hong; Zhou, Kun
Fructus Psoraleae (FP), widely used in traditional medicine, is increasingly reported to cause serious hepatotoxicity in recent years. However, the main toxic constituents responsible for hepatotoxicity and the underlying mechanisms are poorly understood. In the present study, psoralen, a main and quality-control constituent of FP, was intragastrically administered to Sprague-Dawley rats at a dose of 60 mg/kg for 1, 3 and 7 days. Blood and selected tissue samples were collected and analyzed for biochemistry and histopathology to evaluate hepatotoxicity. The results showed that psoralen could induce hepatotoxicity by enhanced liver-to-body weight ratio and alterations of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total cholesterol after administration for 3 days. In addition, histopathological examinations also indicated the hepatotoxicity induced by psoralen. Furthermore, the mRNA and protein levels of hepatic bile acid transporters were significantly changed, in which MRP4, ABCG5 and ABCG8 were repressed, while the protein level of NTCP tended to increase in the rat liver. Taken together, psoralen caused liver injury possibly through affecting bile acid transporters, leading to the disorder of bile acid transport and accumulation in hepatocytes.